Utilizing the AR and mobile apps to show the rhetorical miracle of the fetal growth stages according Quran - Syarilla Iryani, A. Saany; Elsayed Mohamed Salem, Salem Elawadi; Mohd Hafiz, Yusoff@Che Abdullah (2020)
The Qur'an-based Fetal/Fetus growth using Augmented Reality (AR) was produced for teenagers, adults and mothers to learn the Quran-based Fetal development and learn more efficiently in school. Current learning strategies are changed by AR developments and the use of mobile phones. This app might have the option to help individuals learn about the evolution of the Quran-based Fetal that is increasingly intuitive and enjoyable. Likewise, this app will use 3-D smart elements, a sound, and display information with the goal of individuals making sure to use this app. ADDIE technology is separated into five main areas, namely the beginning of the examination stages, planning stages, improvement stages, implementation stages and evaluation stages. Using the ADDIE strategy ensures that the progress of the tire works easily and in order. This application supported by the different three languages which are Arabic, English and Malay language.